Liberal world order and its critics civilisational states and cultural commonwealths - Pabst, Adrian (World politics and dialogues of civilizations series, 2019)
This provocative book contends that the liberal world order is illiberal and undemocratic – intolerant about the cultural values of ordinary people in the West and elsewhere while concentrating power in the hands of unaccountable Western elites and Western-dominated institutions.